The Importance of Teaching Creative Writing in English Classes - Ismoilova Mamlakat Qurbonovna; Kamolova Shaxlo Ubaydillo qizi (Genius Journals, 2021)
Writing is a complex process that requires the author to be aware of and combine various components of language successfully Creativity in the Classroom explores how to support creativity across the curriculum in multiple content areas, including language arts, social studies, science, and mathematics.
Keywords: Writing; Creativity; language; Excellence in Arts Education